LOYALITAS PELANGGAN PT NABAWI MULIA PENDEKATAN KUALITATIF DAN KUANTITATIF MENGGUNAKAN PLS SEM - Santosa, Agus Djoko; Nilawati, Evi; Maryanto, Rudi Dwi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Opportunities for the magnitude of consumer interest are utilized as optimally as possible by the organizers of the umrah and hajj pilgrimage, taking into account the important factor is customer loyalty, customer loyalty is the driving force to go forward in supporting the development of religious tourism services. Customer loyalty, related to the perception of the perpetrators or consumers, where the higher the services of the service institutions to the consumer, give a high value of behavior to recommend to others, in the form of written promotions, or through word of mouth, called words to mouth. Many factors affect customer loyalty, including internal price organizers. Research on the factors that influence customer loyalty is approached by two cauldron methods and I use NVivo and PLS2. The main purpose of this study as a form of service in an effort to improve consumer service strategies at the Umrah and Hajj service institute, PT Nabawi Mulia.